1990
DOI: 10.1111/j.1745-459x.1990.tb00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Terminology to Describe the Handfeel Properties of Paper and Fabrics

Abstract: ABSTRACT. Understanding the tactile feel of paper, nonwoven, and woven products requires a valid and reliable sensory evaluation method which discriminates and describes handfeel properties. The Handfeel Spectrum Descriptive Analysis method separates the sensory tactile properties of paper and fabrics into clearly defined characteristics that are based on sound physical properties. The benefit of using a trained descriptive sensory panel is that resulting analytical sensory data allow full documentation of a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…The first phase of the work has concentrated on setting up representations of simple mechanical variables using existing hardware and established software tools 7 . Logitech's Wingman mouse has been chosen as a low-cost haptic interface device.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first phase of the work has concentrated on setting up representations of simple mechanical variables using existing hardware and established software tools 7 . Logitech's Wingman mouse has been chosen as a low-cost haptic interface device.…”
Section: Methodsmentioning
confidence: 99%
“…touchstroke. 5,6,7 Touch Evaluation A procedure was developed to allow a restricted form of tactile evaluation which would simulate as closely as possible the conditions under which the Wingman mouse would be used. This procedure is summarised below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Civille and Dus [9] reviewed previously published studies on the development of sensory handfeel attributes, terminology, and systems. Confirming several earlier analyses [6,7,18] they concluded that there were significant deficiencies in the published methods in terms of the development of primary (discrete and independent) tactile characteristics, the operationalization of terminology and evaluation procedures, proper scaling methodology, subject/panelist training, and general test protocols and controls.…”
Section: Recent Developments In Sensory Descriptive Handfeel Analysismentioning
confidence: 99%
“…While the next 50 years produced a growing volume of literature on these topics, the study of the human responses to clothing materials suffered from a lack of theoretical models to guide research in the field. As a result, the field was plagued by idiosyncratic and undefined terminology, a lack of operational constructs, confusion over the type of panelists to use, failure to adopt modern psychophysical techniques, and general confusion in communication about fabric attributes and qualities [6][7][8][9].…”
Section: General Backgroundmentioning
confidence: 99%